PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP REWARD DI SEKOLAH DASAR NEGERI KECAMATAN KEBON JERUK DAN CENGKARENG - Neneng Masnawati (Jurnal Manajemen Pendidikan, 2018)
The purpose of this research is to determine the effect of leadership and organizational climate on reward school community elemtary school in village of kebon jeruk and cengkareng..The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) leadership has a positive direct effect in reward, (2) organizational climate has a positive direct effect in reward, (3) leadership has a positive direct effect in organizational climate.